Enriched sensory feedback delivered during a voluntary action boosts subjective time compression - Ueda, Sayako; Shimoda, Shingo (Frontiers in Psychology, 2023)
Introduction The subjective experience of time can be influenced by various factors including voluntary actions. In our previous study, we found that the subjective time experience of an action outcome can be compressed when an individual performs a continuous action compared to a single action, suggesting that the sense of agency (SoA), the feeling of control over one’s own action outcomes, contributes to the subjective time compression. We hypothesized that enhancing SoA by providing sensory feedback to participants would further compress the subjective time experience. Methods To test the hypothesis, we used a temporal reproduction task where participants reproduced the duration of a previously exposed auditory stimulus by performing different voluntary actions: a combination of single actions with single auditory feedback, continuous action with single auditory feedback, or continuous action with multiple auditory feedback. Results The results showed that the continuous action conditions, regardless of the type of auditory feedback, led to a compression of the subjective time experience of the reproduced tone, whereas the single action condition did not. Furthermore, a greater degree of subjective time compression during continuous action and a stronger SoA were revealed when enriched with multiple auditory feedback. Discussion These results indicate that enriching auditory feedback can increase subjective time compression during voluntary action, which in turn enhances SoA over action outcomes. This suggests the potential for developing new techniques to artificially compress the subjective time experience of daily events.